Combined beach - inner shelf erosion in short and medium term (Maspalomas, Canary Islands) (2012)
The analysis of the accurate topo-bathymetric digital elevation model (DEM), the cartography of the submarine sedimentary cover and the monitoring of short (seasonal) and medium-term (2000-2009) morphological changes have permitted depicting the erosional trend in the short and medium-term of the Maspalomas sedimentary system. Short-term analysis showed intense sedimentary fluxes between the beaches and the inner shelf, and sedimentary exchanges with other sectors of the inner shelf, while the steep slope inner shelf fronting La Bajeta cape was identified as a sink area. In the medium-term the sediment budget showed high erosion of the supratidal and intertidal sectors of the beaches due to storm waves in the 2005-2006 winter, followed by accretion over the next four years, but which did not reach the initial sedimentary state. The inner shelf and subtidal sector of the beaches showed negative budgets in the short and medium-term. Interannual variability of the wave and wind regimes determines decadal beach erosion-accretion cycles, while long-term climatic change, evidenced at the study area by a decrease of trade winds and NE wave intensity in 2005, is expected to produce a possible increase of erosion at the El Inglés inner shelf and consequently a decrease in sediment inputs to the El Inglés beach and Maspalomas dune field. Finally, the influence of the geological heritage is depicted by the Fataga gully’s control of the present coastal morphology, and by the island relief control of the wind, waves and current directions in the study area.